Parental incarceration as a predictor of developmental trajectories of externalizing behaviors across adolescence. (August 2019) - Kjellstrand, Jean; Yu, Gary; Eddy, J. Mark
Abstract: With nearly 3 million minor children experiencing parental incarceration on any given day, interest on the impact of this incarceration on children has intensified. Of particular interest is the link between parental incarceration and the development of child externalizing behaviors. While research in this area has expanded, more research is needed that examines the differential effects of parental incarceration and the heterogeneity of outcomes for children. The current study examines specific developmental trajectories of externalizing behaviors and the impact of parental incarceration on trajectory membership when controlling for key individual, family and parental influences. While the results suggest there are several developmental pathways for externalizing behaviors, parental incarceration was a significant risk factor for only one of the three problematic pathways. The study emphasizes some of the protective and risk factors for different patterns of development, specifically the role of parental incarceration. Such information is critical in the development of targeted prevention and intervention programs to support youth and their families impacted by parental incarceration. Highlights: Earlier research identified four developmental trajectories for externalizing behaviors. The study examines how parental incarceration predicts trajectory membership. Parental incarceration was a key predictor for one of the problematic pathways. The study identified additional significant predictors of trajectory membership. Predictors included trauma, discipline, mother/child relationship, maternal depression.